Unpacking Codes and Meanings in Blink Twice (2024): A Barthesian Semiotic Analysis (Sastra Inggris UNPAM, 2025)
This study aims to examine the types of code and their implied meanings in Zoe Kravitz’s film Blink Twice through the lens of semiotic analysis. Utilizing Roland Barthes’s five-code theory (1974), the research investigates how various narrative codes operate within the film’s visual and verbal elements to convey layered meanings. In semiotics, a code is understood as a structured system of signs that communicates meaning—whether through objects, gestures, language, or visual elements. Codes can appear in both verbal and nonverbal forms, making them ubiquitous in cinematic storytelling.This study employs a qualitative descriptive approach, analyzing 19 selected data points consisting of both visual and verbal codes from the film. These codes are categorized according to Barthes’s five narrative codes: 5 hermeneutic codes (enigma or mystery elements), 3 proairetic codes (sequential action-driven cues), 2 semantic codes (connotative meanings in dialogue or text), 7 symbolic codes (associated with objects, colors, gestures, or costumes), and 2 cultural codes (references tied to broader cultural knowledge or norms). The findings are systematically presented in tabular form, outlining the frequency and function of each code type. The analysis reveals that Blink Twice constructs meaning through a complex interplay of these narrative codes, inviting viewers to interpret hidden messages embedded within the film’s visuals and dialogue. The study concludes that Barthes’s semiotic framework is effective for decoding the multilayered communication strategies used in contemporary cinema, particularly in films that engage with cultural, psychological, and gender-related themes.